The risk of unexpected hospital admissions and primary care visits after an elective day‐case gastroscopy: a cohort study within England. Issue 1 (21st April 2022) - Crooks, Colin J.; Card, Timothy R.; West, Joe
Summary: Aim: To determine the excess of acute medical contacts following a day‐case diagnostic gastroscopy. Methods: Cohort study using English linked primary, secondary care and death registry electronic health data. We included 277, 535 diagnostic day‐case gastroscopies in 225, 304 people between 1998 and 2016 and followed up for 30 days. 1, 383, 535 30‐day periods without a gastroscopy within 991, 249 people frequency matched on year, gender and decade of birth. Non‐cancer deaths, emergency non‐cancer admissions and cardio, vascular or respiratory (CVR) primary care consultations were identified and adjusted for each other as competing risks. Outcomes related to possible indications for gastroscopy were censored. Results: 5.1% of day‐case diagnostic gastroscopies were followed by emergency hospital admission, 0.4% for a CVR diagnosis. Adjusted for age, sex, morbidity, time trends, indications and competing risks, there was a 0.1% excess of CVR‐related hospital admissions compared to controls. This reduced to 0.05% (95% confidence interval 0.04–0.06%) in people under 40 years without morbidity and increased to 1.1% (0.6%–1.6%) in people over 90 years with high comorbidity. Similarly, by 30 days, 3.8% had a primary care consultation for a CVR problem, with an excess after adjustment ranging from 0.13% (0.11%–0.16%) to 0.31% (0.14%–0.50%). Overall numbers needed to harm ranged from 1 in 294 gastroscopies to 1 in 67 gastroscopies. Conclusions: There was an excess of vascular and respiratory events associated with a diagnostic gastroscopy. In younger patients, this risk manifested as an increase in primary care consultations while in older patients there was an increase in emergency hospital admissions. Abstract : Number of day case diagnostic gastroscopies needed to harm ‐ excess emergency admissions for cardio, vascular or respiratory diagnoses within 30 days of the procedure.